2013
DOI: 10.1088/1475-7516/2013/08/002
|View full text |Cite
|
Sign up to set email alerts
|

Dark matter and dark energy from quark bag model

Abstract: We calculate the present expansion of our Universe endowed with relict colored objects -quarks and gluons -that survived hadronization either as isolated islands of quarkgluon "nuggets" or spread uniformly in the Universe. In the first scenario, the QNs can play the role of dark matter. In the second scenario, we demonstrate that uniform colored objects can play the role of dark energy providing the late-time accelerating expansion of the Universe.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 35 publications
(61 reference statements)
0
45
0
Order By: Relevance
“…It is observed that to describe a stellar model made of strange quark matter well known MIT bag EOS can be considered under such a situation. Successful use of the MIT bag EOS to describe strange quark stars the following recent works are available in the literature [31,32,33,34,35,36,37,38]. This type of simplest form of EOS is very useful to study equilibrium configuration of a compact stellar object made of only up, down and strange quarks even in the framework of general relativity without invoking any quantum mechanical particle physics aspect.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that to describe a stellar model made of strange quark matter well known MIT bag EOS can be considered under such a situation. Successful use of the MIT bag EOS to describe strange quark stars the following recent works are available in the literature [31,32,33,34,35,36,37,38]. This type of simplest form of EOS is very useful to study equilibrium configuration of a compact stellar object made of only up, down and strange quarks even in the framework of general relativity without invoking any quantum mechanical particle physics aspect.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the proposal by [1], which can be considered as part of the stream of unified dark matter models, has been suggested to explain the nature of DM and the present cosmic acceleration. Such suggestion arises from the hypothesis that a small part of quarks and gluons did not yield to hadronization, and resisted either as isolated aggregates of quark-gluon nuggets (QNs) or as a perfect fluid in the form of a quark-gluon plasma (QGP) (uniformly spread on cosmological scales).…”
Section: Introductionmentioning
confidence: 99%
“…A recent work [42] explored the possibility that the QGP fluid acted as DM in galactic halos concluding that the corresponding rotation curves were reasonable. At the cosmological level, a QGP fluid was first considered to mimic DM in [1].…”
Section: Introductionmentioning
confidence: 99%
“…There is a number of interesting modifications [1,2,[26][27][28][29][30]. In our paper [8], we considered two possible forms of the equation of state. The corresponding total background pressure 2 and energy density of all nuggets in the Universe, as well as their temperature, read, respectively,…”
Section: Quark-gluon Nuggetsmentioning
confidence: 99%